Revitalisasi Proses Peneguhan Akidah dalam Menghadapi Cabaran Pascamodenisme - Dato' Zakaria Stapa (Ar-Raniry: International Journal of Islamic Studies, 2014)
Pascamodenisme had been actively sneaking in all sectors of life and leads to a change in setting values and lifestyle. As willingly to lerated,if it controlled atmosphere and pulse Western life, it is also certainlyappears to be an image and the image is immediately admired and exportedto all of the world, including the Muslim world, in various means andchannels. The danger is two-dimensional generated by secularization onthe one hand, and bribes pascamodenisme value which is also the last issueof secularism itself is spread widely through the process of globalization.To restore this condition, the passage must necessarily be given to thecreed to play a memorable role as an identity forming and the identity insociety. In addition, the process also needs to be given in solid supportwithout split by major institution in society, especially in family institution,educational institution-formal and informal –social growth, empire and themass media.